Anna's special present - Tsutsui, Yoriko (New York : Puffin Books, 1990)
Anna hates it when her little sister Katy begs to play with her favorite doll; but, when Katy is sick in the hospital, Anna knows just right gift to cheer her.
Keywords: Sisters--Fiction; Dolls--Fiction; Sickness--Fiction